The Impact of Qigong and Tai Chi Exercise on Drug Addiction: A Systematic Review and Meta-Analysis - Cui, Jiabao; Liu, Fang; Liu, Xuan; Li, Ru; Chen, Xiaorong; Zeng, Hongfa (Frontiers in Psychiatry, 2022)
Background: Previous preliminary studies have found that qigong exercises produced significant effects in healthy people and in various clinical populations. The purpose of this study was to systematically review the effects of qigong and tai chi exercise on individuals with drug addiction. Methods: A systematic search of seven English databases and three Chinese databases was conducted to identify randomised controlled trials (RCTs) and non-randomised comparative studies (NRS) assessing the effects of qigong and tai chi on drug addiction. Study quality was assessed using the Checklist for the Evaluation of Non-Pharmaceutical Trial Reports (CLEAR-NPT). Results: Two RCTs and nine NRS studies were included in this study, including a total of 1072 patients with drug addiction (age range, 27–43 years). The results showed that qigong and tai chi exercise had a significant overall effect on depression, anxiety, quality of life, and sleep quality. The subgroup analysis found that qigong outperformed tai chi on the improving depression (SMD = -0.353, 95%CI [-0.548, -0.159]), anxiety (SMD = -0.541, 95%CI [-0.818, -0.264]), and sleep quality (SMD = 0.673, 95%CI [0.438, 0.907]). Conclusion: Existing studies suggest that qigong and tai chi are effective at improving depression, anxiety, and quality of life in drug users; however, the evidence from rigorous randomised controlled group trials is lacking.